Micropropagation, myristicin production enhancement, and comparative GC-MS analysis of the n-hexane extracts of different organs of Daucus pumilus (Gouan), family Apiaceae - Asmaa M Arafa; Afaf E Abdel-Ghani; Samih I El-Dahmy; Sahar Abdelaziz (Wolters Kluwer Medknow Publications, 2020)
Aim: This work aimed to study the somatic embryogenesis and organogenesis of endangered Daucus pumilus (Gouan) for the conservation of this plant and improving the production of secondary metabolites of medicinal value. Materials and Methods: The callus formation and in vitro propagation of D. pumilus (Gouan) by using a different combination of naphthalene acetic acid and benzylaminopurine were established. Various embryogenic stages were tracked using scanning electron microscopy and light microscopy. The volatile constituents of the n-hexane extracts of D. pumilus (Gouan) that extracted by ultrasonic-assisted technique were analyzed by gas chromatography-mass spectrometry. Results and Discussion: Somatic embryogenesis and organogenesis of endangered D. pumilus (Gouan) were established for the first time. Myristicin and elemicin were successfully increased during micropropagation to 70.89% and 2.19%, respectively. Furthermore, the induction of compounds such as 6-methoxymellein, eugenin, methyl behenate, and 1,6-dimethylnaphthalene was also detected. Conclusion: Commercially, this protocol decreases the dependence on wild medicinal plants, enhances the manufacturing of valuable phytochemicals to meet the great demands of the pharmaceutical industries, and acts as a mean for genetic transformation of this plant.